HUBUNGAN UMUR KEHAMILAN DENGAN STATUS KESEHATAN GINGIVA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS ANDALAS KECAMATAN PADANG TIMUR - Kinanti Fauzin; Hafni Bachtiar; Susi Susi (Faculty of Dentistry Universitas Andalas, 2015)
Gingivitis is an inflammation of the soft tissues inoral cavity that invade the free gingival. There are two kinds of etiologies that can cause gingivitis, they are plaque and non-plaque. Pregnant women will have some maternal physiological changes during pregnancy, one of them is the increasing of estrogen and progesterone. It will cause the gingival tissue to react to irritant such as plaque excessively. The aim of this study was to determine the relationship between gestational age and gingival index in pregnant women. This analytic correlation research used cross sectional approach. The gestational age were observed from Mom’s and Kid’s Health Book. The Gingival Index was observed by using Loe and Silness index to each pregnant woman’s oral cavity. Data was analysed by using Chi –square. The study took place in Andalas Public Health Center, from 16th February 2-15 until 26th February 2015. Most of the pregnant women had mild gingivitis, no pregnant women were found with healthy gingiva or severe gingivitis. The result showed that there was no significantly relationship between gestational age and gingival index in pregnant women (p>0,005).